2006
DOI: 10.1161/01.hyp.0000203148.42892.7a
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Mechanisms of Eplerenone on Cardiac Performance and Remodeling in Failing Rat Hearts

Abstract: Abstract-Aldosterone may play a pivotal role in the pathophysiology of heart failure. To elucidate the beneficial cardioprotective mechanism of eplerenone, a novel selective aldosterone blocker, we hypothesized that eplerenone stimulates endothelial NO synthase (eNOS) through Akt and inhibits inducible NO synthase (iNOS) via nuclear factor B (NF-B) after the development of oxidative stress and activation of the lectin-like, oxidized, low-density lipoprotein receptor 1 (LOX-1) pathway in Dahl salt-sensitive rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 38 publications
5
83
0
1
Order By: Relevance
“…2,3 This damage seems to be aldosterone mediated, and aldosterone blockade with mineralocorticoid receptor (MR) antagonists, such as spironolactone, may prevent the onset of these effects. 4,5 On the other hand, it cannot completely be ruled out that potassium and high blood pressure also play additional key roles in this damage. 6,7 This evidence has impressively been supported by clinical studies, such as the Randomized Aldactone Evaluation Study and the Eplerenone Post-Acute Myocardial Infarction Survival and Efficacy Study.…”
mentioning
confidence: 99%
“…2,3 This damage seems to be aldosterone mediated, and aldosterone blockade with mineralocorticoid receptor (MR) antagonists, such as spironolactone, may prevent the onset of these effects. 4,5 On the other hand, it cannot completely be ruled out that potassium and high blood pressure also play additional key roles in this damage. 6,7 This evidence has impressively been supported by clinical studies, such as the Randomized Aldactone Evaluation Study and the Eplerenone Post-Acute Myocardial Infarction Survival and Efficacy Study.…”
mentioning
confidence: 99%
“…MR is a metabolic nuclear receptor that plays a key role in the regulation of electrolyte homeostasis and blood pressure in the body [12] . MR activation mediates inflammation, proliferation and fibrosis [29,39,40] , while MR blockade exhibits beneficial effects on cardiovascular morbidity and mortality in patients with heart failure [41,42] . Recent studies have also shown that MR antagonists improve adipocyte dysfunction and insulin resistance in obese mice [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…NAD(P)H oxidase p22 phox , p47 phox , gp91 phox , tumor necrosis factor-(TNF-), interleukin-1 (IL-1 ), monocyte chemoattractant protein-1 (MCP-1), procollagen type and , and fibronectin protein expressions were measured as described previously [18][19][20] . LV was homogenized (25% wt/vol) in 10 mmol/l HEPES buffer, pH 7.4, containing 320 mmol/l sucrose, 1 mmol/l EDTA, 1 mmol/l DTT, 10 g/ml leupeptin, and 2 g/ml aprotinin at 0 to 4 with a polytron homogenizer.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Histological detection of superoxide anion in the LV was performed using dihydroethidium (DHE) as described previously 18,19,21,23) .…”
Section: Detection Of Superoxide Anion In the LVmentioning
confidence: 99%
See 1 more Smart Citation